Polymer electrolyte and preparation method thereof

By introducing hyperbranched polymer grafted modified nanosilicon dioxide into polymer electrolytes, the compatibility and conductivity problems of composite polymer electrolytes when organic and inorganic are solved, and the dual improvement of conductivity and mechanical properties is achieved, and it is suitable for high-performance lithium-ion batteries.

CN119627207APending Publication Date: 2025-03-14GUANGDONG POWER GRID CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411801084.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When the existing composite polymer electrolytes combine organic and inorganic phases, their compatibility, dispersion and interface stability are not ideal, which affects their conductive and mechanical properties.

Method used

Hyperbranched polymer grafted modified nanosilica is introduced into the polymer matrix as a functional composite component. Through surface modification and hyperbranched polymer grafting, the compatibility and conductivity of nanosilica are improved.

Benefits of technology

It significantly improves the conductivity and mechanical properties of polymer electrolytes, extends service life, and improves electrochemical stability. It is suitable for high-performance new polymer lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178066250000081
    Figure BDA0005178066250000081
  • Figure BDA0005178066250000091
    Figure BDA0005178066250000091
  • Figure BDA0005178066250000092
    Figure BDA0005178066250000092
Patent Text Reader

Abstract

The invention discloses a polymer electrolyte and a preparation method thereof, and belongs to the technical field of materials.According to the polymer electrolyte, specific hyperbranched polymer grafted modified nano silicon dioxide is introduced into a polymer matrix to serve as a functional compound component, the conductivity and mechanical performance of the whole component can be effectively improved, and the product is long in service life and low in cost. And the polymer lithium ion battery has high electrochemical stability and is very suitable for various novel polymer lithium ion batteries with high-performance requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a polymer electrolyte and a preparation method thereof. Background Art

[0002] As an important component of the new polymer lithium-ion battery, polymer electrolytes can be divided into four categories: all-solid, gel, composite and single-ion. All-solid polymer electrolytes have high mechanical strength but low ionic conductivity, while gel polymer electrolytes have high conductivity but poor mechanical properties. Single-ion polymer electrolytes have high lithium ion transmission efficiency by limiting the movement of anions, but the conductivity is generally not high at room temperature. Composite polymer electrolytes are made by adding inorganic nanoparticles to the polymer matrix to take into account both the ionic conductivity and mechanical properties of the product. However, in the actual research and development process, people found that due to the differences between the organic phase and the inorganic phase, the compatibility, dispersibility and interface stability of the two after combination are not ideal. At the same time, the introduction of inorganic particles has a great influence on the ionic conductivity of the electrolyte, and the actual comprehensive performance of the product still needs to be improved. Summary of the invention

[0003] Based on the defects of the prior art, the purpose of the present invention is to provide a polymer electrolyte. This product can effectively improve the conductivity and mechanical properties of the overall components by introducing specific hyperbranched polymer grafted modified nano-silica as a functional compounding component into the polymer matrix. The product has a long service life and high electrochemical stability, and is very suitable for various new polymer lithium-ion batteries with high performance requirements.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] A polymer electrolyte comprising a polymer matrix, a lithium salt and a modified inorganic component;

[0006] The modified inorganic component includes hyperbranched polymer grafted modified nano-silica;

[0007] The hyperbranched polymer grafted modified nano-silica is obtained by grafting modified nano-silica with N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester through hyperbranched polymerization;

[0008] The modified nano silicon dioxide is surface-modified nano silicon dioxide obtained by coupling gamma-aminopropyltriethoxysilane and methyl methacrylate.

[0009] Traditional composite polymer electrolytes generally use blending, copolymerization and other methods to fill inorganic particulate materials in polymer matrices and lithium salts to improve the mechanical properties of the overall product, but such practices often bring about problems such as low organic-inorganic compatibility and poor interface stability, which may not only fail to achieve the expected improvement in mechanical strength, but may even affect the conductive properties of the product. For this reason, in the technical solution of the present invention, when the polymer electrolyte introduces inorganic nano-silicon dioxide, the component is pre-specially surface-modified and hyperbranched polymer grafted. The hyperbranched polymer itself has an amorphous aggregation state, rich functional groups and low viscosity, and has high compatibility with the matrix in the polymer electrolyte and can even replace the conventional matrix. However, the mechanical properties of this type of component are poor and cannot be used alone. Therefore, after being grafted on the surface of nano-silicon dioxide as a modified component, the organic-inorganic composite filler formed promotes the dissociation of lithium salts in the polymer matrix based on the high branching degree and rich functional groups of the hyperbranched polymer, while enhancing the mobility of the polymer chain segments, and significantly improving the ionic conductivity of the electrolyte. In addition, the introduction of nano-silica not only enhances the mechanical properties of the electrolyte, but also further enhances the conductivity of the electrolyte by improving the dissociation efficiency of the lithium salt. Through the synergistic effect of the two, the mechanical properties and conductivity of the overall polymer electrolyte are effectively improved. If the hyperbranched polymer is not introduced, and only pure nano-silica or traditional coupled modified nano-silica is used, the same enhancement effect cannot be achieved.

[0010] However, unlike traditional organic grafting, the hyperbranched polymerization grafting modification of nano-silica by N,N-dihydroxyethyl-3-aminomethyl propionic acid methyl ester of the present invention needs to be achieved by generating hyperbranched polyamine-ester through reaction, and for this reason, the surface of nano-silica needs to be pre-modified in advance: the methyl ester group formed after coupling modification by small molecule coupling agent γ-aminopropyl triethoxysilane (KH-550) and methyl methacrylate (MMA) can provide a reaction starting core for the hyperbranched monomer N,N-dihydroxyethyl-3-aminomethyl propionic acid methyl ester, thereby causing polymerization condensation growth and finally completing the grafting. If the surface modification treatment in the early stage is not carried out, the grafting efficiency of the hyperbranched polymer will be low, and the performance of the final product will not be as expected.

[0011] Preferably, the N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester is prepared by the addition reaction of methyl methacrylate and diethanolamine (DEA).

[0012] More preferably, the mass ratio of methyl methacrylate to diethanolamine is (0.8-1.2):(0.8-1.2), the temperature during the addition reaction is 35-45° C., and the time is 6-10 days.

[0013] The AB2 type hyperbranched monomer N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester can be directly prepared by Michael addition reaction of MMA and DEA, but it should be noted that, according to actual conditions, those skilled in the art can also prepare N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester by other methods. Based on the structural clarity of the synthetic product, it is not limited to a certain preparation method under specific conditions.

[0014] Preferably, when the nano-silica is subjected to coupling surface modification, the molar ratio of γ-aminopropyltriethoxysilane to methyl methacrylate is 1:(1.8-2.2).

[0015] More preferably, the mass ratio of the nano-silica to γ-aminopropyltriethoxysilane is 1:(1.8-2.2).

[0016] The modification is carried out by introducing an appropriate amount of small molecule coupling agent. In the modification stage, γ-aminopropyltriethoxysilane first acts on the surface of nano-silica and introduces amino groups, and then connects with methyl methacrylate through the amino groups to provide group sites for the subsequent formation of hyperbranched polyamine-ester. If it is not introduced too much or too little, the subsequent hyperbranched monomer polymerization effect is not good, and the electrochemical performance improvement effect and synergistic effect of the final grafted modified nano-silica after the introduction of the product are not ideal.

[0017] More preferably, the preparation method of the modified nano-silica is:

[0018] Nano-silica and γ-aminopropyltriethoxysilane are dispersed in a solvent, then mixed and reacted at 90-110° C. for 10-15 hours, methyl methacrylate is added, mixed and reacted at 35-45° C. for 6-10 days, filtered, dried and impurities removed to obtain the modified nano-silica.

[0019] Preferably, the preparation method of the hyperbranched polymer graft-modified nano-silica is:

[0020] N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester, modified nano-silica and p-toluenesulfonic acid are mixed, and then vacuum reacted at 55-65° C. for 0.5-1.5 h. The obtained mixture is heated to 75-85° C. for a second reaction for 1.5-2.5 h, then heated to 95-105° C. for a third reaction for 1.5-2.5 h, and finally heated to 115-125° C. for a fourth reaction for 3.5-4.5 h. The obtained product is washed, impurity-removed, dried and sieved to obtain the hyperbranched polymer grafted modified nano-silica.

[0021] More preferably, when the hyperbranched polymer grafted modified nano-silica is prepared, the mass percentage of p-toluenesulfonic acid in the N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester, modified nano-silica and p-toluenesulfonic acid is 0.4-0.6%.

[0022] Preferably, the mass ratio of the N,N-dihydroxyethyl-3-aminomethylpropionate to the modified nano-silica is 10:3 to 10:4.

[0023] Different amounts of grafted materials and grafted materials introduced will affect the grafting efficiency, grafting amount and product dispersion uniformity of the prepared modified inorganic component. The inventors have found through experiments that when the ratio of the above two raw materials in the preparation of the modified inorganic component is in line with the preferred range, the preparation effect is better, and the obtained product has a better effect on improving the conductivity and mechanical properties of the product when used in polymer electrolytes.

[0024] Preferably, the lithium salt includes at least one of LiClO4, LiPF6, LiCF3SO3, LiBF4, LiAsF6, LiN(CF3SO2)2(LiTFSI), and LiBO3.

[0025] Preferably, the polymer matrix includes at least one of PVA (polyvinyl alcohol), PEO (polyethylene oxide), PPG (polypropylene glycol phenolic), PCL (polystyrene), PVDF (polyvinylidene fluoride), and PC (polycarbonate).

[0026] Based on the preference for introducing the modified inorganic component of the hyperbranched polymer grafted modified nano-silica described in the present invention, the polymer electrolyte can select the conventional types used by technicians in this field when selecting the polymer matrix and lithium salt. Compared with existing products that do not introduce the modified inorganic component or introduce traditional inorganic components, both ion / electronic conductivity and mechanical properties can be improved.

[0027] Preferably, the polymer electrolyte comprises the following components in parts by weight based on 100 parts:

[0028] 25-35 parts of lithium salt, 5-30 parts of modified inorganic component and the balance of polymer matrix.

[0029] More preferably, the weight proportion of the modified inorganic component is 15 to 20 parts.

[0030] After adding the modified inorganic component to the polymer electrolyte, the inventors found that as the amount of the component added changes, the conductivity and mechanical properties of the product will also have certain differences. When the amount of the modified inorganic component added is small, the degree of improvement of the conductivity and mechanical properties of the product is low, resulting in low conductivity, large modulus, and small elasticity of the product. With the introduction of the modified inorganic component, based on the synergistic effect of the modified nano-silica and the hyperbranched polymer, the conductivity of the product is significantly improved, and at the same time, the interaction effect between the polymer matrix molecular chain and the modified inorganic component is better, the modified inorganic component particles have favorable slippage in the matrix, and the modulus is greatly reduced, so the elasticity of the product is also improved; and when the amount of the modified inorganic component added is further increased, the intermolecular hydrogen bonding effect of the hydroxyl groups on its surface increases, some particles agglomerate, and the degree of interaction with the polymer matrix becomes weaker, and the overall particle adhesion of the product is also improved, so the modulus increases and the elasticity decreases. When the weight fraction of the modified inorganic component is preferably within the above range, the obtained product can achieve a better comprehensive effect.

[0031] Another object of the present invention is to provide a method for preparing the polymer electrolyte, comprising the following steps:

[0032] The components are mixed in a solution, ultrasonically dispersed, and then placed in a mold for vacuum drying to obtain the polymer electrolyte.

[0033] The polymer electrolyte preparation method of the present invention has simple steps, low requirements on equipment, and can realize industrial-scale production.

[0034] Preferably, the solution comprises at least one of dimethyl sulfoxide, N,N-dimethylformamide, acetone and tetrahydrofuran.

[0035] Another object of the present invention is to provide a lithium ion battery comprising the polymer electrolyte of the present invention.

[0036] The polymer electrolyte of the present invention has ideal conductivity and mechanical properties and is very suitable for novel polymer lithium-ion batteries.

[0037] The beneficial effect of the present invention is that the present invention provides a polymer electrolyte, which can effectively improve the conductivity and mechanical properties of the overall components by introducing specific hyperbranched polymer grafted modified nano-silica as a functional compounding component in a polymer matrix. The product has a long service life and high electrochemical stability, and is very suitable for new polymer lithium-ion batteries with various high-performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a graph showing the nuclear magnetic resonance test results of the hyperbranched polymer monomer in Example 1.

[0039] Figure 2 It is the DSC test chart of Examples 1 to 3 and 6 in Effect Example 1, the PVA used in Example 1 and the blank control sample, wherein 1 is PVA, 2 is the blank control sample, 3 is the product of Example 1, 4 is the product of Example 2, 5 is the product of Example 3, and 6 is the product of Example 6. DETAILED DESCRIPTION

[0040] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0041] Example 1

[0042] An embodiment of the polymer electrolyte and the preparation method thereof of the present invention comprises the following steps:

[0043] (1) Preparation of modified inorganic components:

[0044] (1.1) Preparation of hyperbranched polymer monomer: 20 g MMA and 20 g DEA were weighed and added to a four-necked flask equipped with a thermometer, a stirrer, and a condenser, and 0.5 wt % sodium ethoxide was added. The temperature was maintained at 40° C. and the reaction was carried out for 7 days. Then, the unreacted product was removed by rotary evaporation in a 60° C. water bath to obtain the hyperbranched monomer N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester. The product was subjected to a nuclear magnetic resonance test, and the results were as follows: Figure 1 As shown, it can be seen that the characteristic peaks of the two active H of the C=C double bond are not seen at the chemical shifts of 5.5ppm and 6.00ppm, which can confirm that MMA and DEL have completely undergone addition reaction;

[0045] (1.2) Preparation of modified nano-silica: hydrophobic nano-silica with an average particle size of 50 nm and commercially available KH-550 were placed in 95% ethanol in a mass ratio of 1:2 and ultrasonically dispersed for 30 minutes, then stirred and reacted at 100° C. for 12 hours in an oil bath. The resulting mixture was recorded as SiO2-KH550. MMA and 0.05 wt % sodium ethoxide were then added, the temperature was lowered to 40° C. and mixed for reaction for 7 days, filtered, dried, placed in a Soxhlet extractor, extracted with ethanol at 100° C. for 48 hours to remove impurities, and dried at 45° C. to obtain the modified nano-silica.

[0046] (1.3) Preparation of hyperbranched polymer grafted modified nano-silica: 3g of modified nano-silica was placed in a four-necked flask equipped with a thermometer, a stirrer, and a condenser, 10g of hyperbranched monomer N,N-dihydroxyethyl-3-aminomethyl propionic acid methyl ester and 0.5wt% of p-toluenesulfonic acid were added, and the mixture was stirred rapidly under vacuum conditions, and the reaction was carried out at 60°C for 1h to further remove the unreacted substances remaining in the monomer, and then the reaction temperature was gradually increased to 80°C for 2h, then raised to 100°C for 2h, and finally raised to 120°C for 4h. Finally, the obtained mixture was used as a solvent, and the ungrafted homopolymer was removed at 80°C in a Soxhlet drawer for 48h. The mixture was dried in vacuum, ground and sieved to obtain the hyperbranched polymer grafted modified nano-silica, which was recorded as SiO2-g-HBPAE;

[0047] (2) Preparation of polymer electrolyte: The modified inorganic component and the polymer matrix PVA (PVA117 produced by Kuraray Co., Ltd., Japan) are mixed in a 10%wt% dimethyl sulfoxide solution of the polymer matrix, and then a lithium salt LiClO4 is added, wherein the weight parts of the modified inorganic component, the polymer matrix and the lithium salt are 5 parts, 65 parts and 30 parts, respectively, based on 100 parts; the obtained mixture is ultrasonically dispersed for 0.5h, stirred at 80°C at a speed of 1000rpm for 2h, and finally poured into a 20×80×5mm silicone rubber mold, and dried at 60°C for 24h and vacuum dried at 100°C for 48h to obtain the polymer electrolyte.

[0048] Example 2

[0049] An embodiment of the polymer electrolyte and preparation method thereof of the present invention is different from Embodiment 1 only in that the weight parts of the modified inorganic component, the polymer matrix and the lithium salt are 10 parts, 60 parts and 30 parts respectively based on 100 parts.

[0050] Example 3

[0051] An embodiment of the polymer electrolyte and preparation method thereof of the present invention is different from Embodiment 1 only in that the weight parts of the modified inorganic component, the polymer matrix and the lithium salt are 15 parts, 55 parts and 30 parts respectively based on 100 parts.

[0052] Example 4

[0053] An embodiment of the polymer electrolyte and preparation method thereof of the present invention is different from Embodiment 1 only in that the weight parts of the modified inorganic component, the polymer matrix and the lithium salt are 20 parts, 50 parts and 30 parts respectively based on 100 parts.

[0054] Example 5

[0055] An embodiment of the polymer electrolyte and preparation method thereof of the present invention is different from Embodiment 1 only in that the weight parts of the modified inorganic component, the polymer matrix and the lithium salt are 25 parts, 45 parts and 30 parts respectively based on 100 parts.

[0056] Example 6

[0057] An embodiment of the polymer electrolyte and preparation method thereof of the present invention is different from Embodiment 1 only in that the weight parts of the modified inorganic component, the polymer matrix and the lithium salt are 30 parts, 40 parts and 30 parts respectively based on 100 parts.

[0058] Comparative Example 1

[0059] A polymer electrolyte and a preparation method thereof, wherein the preparation method of the polymer electrolyte comprises the following steps:

[0060] (1) Nano-silica preparation: prepare hydrophobic solid-phase nano-silica with an average particle size of 50 nm;

[0061] (2) Preparation of hyperbranched polymer grafted nano-silica: 3g of nano-silica was placed in a four-necked flask equipped with a thermometer, a stirrer, and a condenser, 10g of hyperbranched monomer N,N-dihydroxyethyl-3-aminomethyl propionic acid methyl ester and 0.5wt% of p-toluenesulfonic acid were added, and the mixture was stirred rapidly under vacuum conditions, and the reaction temperature was raised to 80°C for 2h, then raised to 100°C for 2h, and finally raised to 120°C for 12h. The resulting mixture was finally treated with acetone as a solvent, and placed in a Soxhlet drawer at 80°C for 48h to remove the ungrafted homopolymer, vacuum dried, ground and sieved to obtain the hyperbranched polymer grafted nano-silica;

[0062] (3) Preparation of polymer electrolyte: Hyperbranched polymer grafted nanosilica and polymer matrix PVA (PVA117 produced by Kuraray Co., Ltd., Japan) are mixed in a 10%wt% dimethyl sulfoxide solution of the polymer matrix, and then lithium salt LiClO4 is added, wherein the weight parts of hyperbranched polymer grafted nanosilica, polymer matrix and lithium salt are 5 parts, 65 parts and 30 parts, respectively, based on 100 parts; the obtained mixture is ultrasonically dispersed for 0.5h, stirred at 80°C at a speed of 1000rpm for 2h, and finally poured into a 20×80×5mm silicone rubber mold, and dried at 60°C for 24h and vacuum dried at 100°C for 48h to obtain the polymer electrolyte.

[0063] Comparative Example 2

[0064] A polymer electrolyte and a preparation method thereof, wherein the preparation method of the polymer electrolyte comprises the following steps:

[0065] (1) Preparation of modified nano-silica: hydrophobic solid-phase nano-silica with an average particle size of 50 nm and commercially available KH-550 were placed in 95% ethanol in a mass ratio of 1:2 and ultrasonically dispersed for 30 minutes, then stirred and reacted at 100° C. for 12 hours in an oil bath, and MMA and 0.05 wt % sodium ethoxide were added to the resulting mixture, cooled to 40° C. and mixed for 7 days, filtered, dried, placed in a Soxhlet extractor, extracted with ethanol at 100° C. for 48 hours to remove impurities, and dried at 45° C. to obtain the modified nano-silica;

[0066] (2) Preparation of polymer electrolyte: modified nano-silica and polymer matrix PVA (PVA117 produced by Kuraray Co., Ltd., Japan) are mixed in a 10%wt% dimethyl sulfoxide solution of the polymer matrix, and then lithium salt LiClO4 is added, wherein the weight parts of modified nano-silica, polymer matrix and lithium salt are 5 parts, 65 parts and 30 parts, respectively, based on 100 parts; the obtained mixture is ultrasonically dispersed for 0.5h, stirred at 80°C at 1000rpm for 2h, and finally poured into a 20×80×5mm silicone rubber mold, and dried at 60°C for 24h and vacuum dried at 100°C for 48h to obtain the polymer electrolyte.

[0067] Effect Example 1

[0068] In order to verify the properties and effects of the polymer electrolyte of the present invention, first, Examples 1 to 3 and 6, the PVA used in Example 1, and a blank control sample (a polymer electrolyte product prepared according to the method of step (2) of Example 1, but without adding a modified inorganic component, and with a weight ratio of polymer matrix to lithium salt of 70 parts:30 parts) were subjected to DSC analysis. The results are as follows: Figure 2 As shown, it can be seen that compared with pure PVA, when lithium salt is introduced, the glass transition temperature of the product drops suddenly from 61.5℃ to 37.6℃, indicating that the polymer matrix and lithium salt have obvious molecular effects. After the introduction of modified inorganic components, the glass transition temperature of the product further drops to -18.2℃. The main reason is that the modified inorganic components contain a large number of hydroxyl groups, which will directly damage the hydrogen bonds between the molecular chains in the polymer matrix. As the amount of modified inorganic components introduced increases further, the glass transition temperature of the product rises to a certain extent, probably due to the agglomeration of these particles. In summary, the modified inorganic components have obvious chemical / physical effects on polymer electrolytes, especially the polymer matrix therein.

[0069] Furthermore, the PVA and the products obtained in Examples 1 to 6 and Comparative Examples 1 to 2 were subjected to temperature-conductivity tests using a conductivity meter. The results are shown in Table 1.

[0070] Table 1

[0071]

[0072]

[0073] As can be seen from Table 1, the polymer electrolyte product prepared according to the present invention has a higher conductivity and a higher conductivity as the temperature increases, compared with comparative examples 1 and 2 and pure PVA products. In the products of Examples 1 to 6, as the amount of the modified inorganic component introduced increases, the conductivity of the product shows a trend of first increasing and then decreasing, indicating that the more the component is added, the better. Among them, the products of Examples 3 and 4 with moderate addition amounts have the best performance, and the conductivity of both is higher than that of other embodiments in different temperature ranges. The main reason is that the organic-inorganic composite filler promotes the dissociation of lithium salts in the polymer matrix based on the high branching degree and functional group richness of the hyperbranched polymer, while enhancing the mobility of the polymer chain segments, significantly improving the ionic conductivity of the electrolyte; but since silicon dioxide is an inorganic component, when the addition amount reaches a certain level, the conductivity of the product will still show a downward trend.

[0074] The product was then subjected to stress-strain test using a tensile testing machine, and the results are shown in Table 2.

[0075] Table 2

[0076]

[0077]

[0078] As can be seen from Table 2, since the modified inorganic component is beneficial to the molecular chain slippage of the polymer matrix, the elastic properties of the product after the introduction of this component are significantly improved, and as the amount of the modified inorganic component added increases, the elasticity of the product gradually increases, and it has a good stress-strain effect when used in lithium-ion batteries. However, as the modified inorganic component is further increased, the elasticity of the product decreases, and the products of Examples 3 and 4 have the best effect.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the present invention.

Claims

1. A polymer electrolyte, characterized in that It includes a polymer matrix, a lithium salt, and a modified inorganic component; The modified inorganic component includes hyperbranched polymer grafted modified nano-silica; The hyperbranched polymer grafted modified nano-silica is obtained by grafting modified nano-silica with N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester through hyperbranched polymerization; The modified nano silicon dioxide is surface-modified nano silicon dioxide obtained by coupling gamma-aminopropyltriethoxysilane and methyl methacrylate.

2. The polymer electrolyte according to claim 1, characterized in that The N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester is prepared by the addition reaction of methyl methacrylate and diethanolamine.

3. The polymer electrolyte according to claim 1, characterized in that When the nano silicon dioxide is subjected to coupling surface modification, the molar ratio of the used gamma-aminopropyltriethoxysilane and methyl methacrylate is 1:(1.8-2.2).

4. The polymer electrolyte according to claim 3, characterized in that The mass ratio of the nano silicon dioxide to gamma-aminopropyltriethoxysilane is 1:(1.8-2.2).

5. The polymer electrolyte according to claim 4, characterized in that The preparation method of the modified nano silicon dioxide is: Nano-silica and γ-aminopropyltriethoxysilane are dispersed in a solvent, then mixed and reacted at 90-110° C. for 10-15 hours, methyl methacrylate is added, mixed and reacted at 35-45° C. for 6-10 days, filtered, dried and impurities removed to obtain the modified nano-silica.

6. The polymer electrolyte according to claim 1, characterized in that The preparation method of the hyperbranched polymer grafted modified nano-silica is: N,N-dihydroxyethyl-3-aminomethylpropionic acid methyl ester, modified nano-silica and p-toluenesulfonic acid are mixed, and then vacuum reacted at 55-65° C. for 0.5-1.5 h. The obtained mixture is heated to 75-85° C. for a second reaction for 1.5-2.5 h, then heated to 95-105° C. for a third reaction for 1.5-2.5 h, and finally heated to 115-125° C. for a fourth reaction for 3.5-4.5 h. The obtained product is washed, impurity-removed, dried and sieved to obtain the hyperbranched polymer grafted modified nano-silica.

7. The polymer electrolyte according to claim 1, characterized in that The mass ratio of the N,N-dihydroxyethyl-3-aminomethyl propionic acid methyl ester to the modified nano silicon dioxide is 10:3 to 10:

4.

8. The polymer electrolyte according to claim 1, characterized in that The lithium salt includes at least one of LiClO4, LiPF6, LiCF3SO3, LiBF4, LiAsF6, LiN(CF3SO2)2, and LiBO3; the polymer matrix includes at least one of PVA, PEO, PPG, PCL, PVDF, and PC.

9. The polymer electrolyte according to claim 1, characterized in that The polymer electrolyte, based on 100 parts, includes the following components in parts by weight: 25-35 parts of lithium salt, 5-30 parts of modified inorganic component and the balance of polymer matrix.

10. A lithium ion battery, characterized in that: The invention comprises the polymer electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Modified polymer electrolyte, preparing method of modified polymer electrolyte and application of modified polymer electrolyte to lithium battery

    CN103985900A